Virtual Open Source environment for training and Simulation of Laparoscopic Surgery - Moreno, Mario R.; Moraes, Thiago Franco; Amorim, Paulo H. J.; Silva, Jorge V. Lopes da; Rodriguez, Ciro A. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2012: Anais do XII Workshop de Informática Médica, 2012)
In the Medical area the use of technological tools for the training process of surgical procedures is an attractive solution, free of risks and implications. In this work the preliminary results of the development of an interactive virtual environment for medical training are exposed. This is developed in the context of an open source simulator of laparoscopic surgery. The geometrical and physical modeling of the anatomical structures or organs involved in surgical procedures are the main focus of this work. Medical images were used to obtain the real anatomical geometries and the Spring-Mass model was applied with a skeleton structure for modeling the mechanical behavior of the soft-tissues. The experimental results for a pancreas are exposed.